On mythologization and globalization in Book for Marko by Svetlana Velmar Janković - Todorov, Vesna B (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
The paper demonstrates how stories in the collection Book for Marko by Svetlana Velmar Janković can be interpreted in two keys: one interpretation key presents these stories as narratives promoting a positive image about what is one’s own, and a negative image about the other, thus contributing to the construction of national identity: in this context the paper focusses on the myth and myth-construction tradition. In another interpretation key the stories in the collection can be understood as narratives promoting culture of dialogue and globalization vision of the world. Thus the paper poses the question "What does the story do?". In answering it, we point to the fact that there exist various cognitive solutions – which of them are to assume relevance depends on the reader’s frame of reference, his moral and cultural principles, as well as his own motives and wishes.